Collapse-resistant design strategy for steel frame structures considering tie force requirements. (September 2022) - Zheng, Yu-hui; Zhong, Wei-hui; Tan, Zheng; Meng, Bao; Duan, Shi-Chao; Zhang, Yue
Abstract: The research on collapse-resistant mechanisms is often focused on the performance of local members, ignoring the impact of these members on surrounding components when the structure bears an external load. Hence, models based on such studies are unable to predict progressive structural failure processes accurately. To avoid progressive collapse, during design, the topology of the structure should be optimized by considering the limit state of constituent columns. In this study, the influence of the tie forces of two-bay beams on the limit states of peripheral frames was analyzed, considering the second-order effect of column failure on surrounding columns. The horizontal constraint requirements of frame columns at different positions were analyzed quantitatively by considering the effect of external loads on the stable bearing capacity of the columns in two stages. The unbalanced bending moment and horizontal tie force are considering in Stages 1 and 2, respectively. Based on this analysis, a design method for creating collapse-resistant structures was proposed, which can identify when additional constraint is required by calculating the maximum tie force exerted on different columns in the structure, while the location and cross-sectional area of reinforcing braces are determined based on the transfer mechanism of the constraint around the column. Finally, the reliability of the design method is verified through a example frame. The braced steel frame designed according to these principles exhibited excellent collapse-resistant performance because the interaction between the structural members and interlocking tensions in different areas of the structure was considered fully, validating the accounting of horizontal tie forces.